Two-way relationship between rheumatoid arthritis and periodontal disease - Mehta, Kinjal J. (International Journal of Research in Medical Sciences, 2017)
The purpose of this literature review to find out what has been reported as a relationship between rheumatoid arthritis and periodontal disease. Both, the periodontal disease and rheumatoid arthritis, are chronic inflammatory diseases and share some common genetic factors. Both of the disease can produce severe destruction of connective tissue through host’s immune response as well as various inflammatory pathways. A thorough literature review has demonstrated that rheumatoid arthritis can impact the severity of periodontitis and has more severe bone and tooth loss. In the same way, people who have periodontal diseases are more prone to developing rheumatoid arthritis, P. gingivalis, which is the key factor in the development of periodontal disease, has an endogenous enzyme which plays a crucial role in the development of the rheumatoid arthritis. The health promotion educational material and campaigns must be conducted to raise awareness and knowledge among professional and general population. Dentists and dental professionals should provide thorough information to their patients. Furthermore, an advanced research should be conducted to find out the type of relationship between RA and periodontal disease.